Children’s Aerobic Fitness and Academic Achievement: A Longitudinal Examination of Students During Their Fifth and Seventh Grade Years - Wittberg, Richard A. (American Public Health Association, 2012)
Objectives. We assessed children’s potential differences in academic achievement based on aerobic fitness over a 2-year period. Methods. The longitudinal study sample included 3 cohorts of students (n = 1725; 50.1% male) enrolled in a West Virginia public school system. Students received baseline fitness and academic assessments as fifth graders and at a 2-year follow-up assessment. We used FitnessGram to assess fitness in aerobic capacity and WESTEST, a criterion-based assessment, for academic performance. Results. Students who stayed in the healthy fitness zone (HFZ) had significantly higher WESTEST scores than did students who stayed in the needs improvement zone (NIZ). Students who moved into or out of the HFZ occasionally had significantly higher WESTEST scores than did students who stayed in the NIZ, but they were rarely significantly lower than those of students who stayed in the HFZ. Conclusions. Students’ aerobic capacity is associated with greater academic achievement as defined by standardized test scores. This advantage appears to be maintained over time, especially if the student stays in the HFZ.